Peningkatan Mutu Transportasi Umum Demi Kenyamanan dan Keamanan Pengguna - Dewa Dwi Putra; Rayhan Dhevano Aufaa; Haura Luthfiyah; Siti Sahara (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Public transportation is a type of public transportation that is used together with crowded people. Public transportation in Indonesia is very diverse, it has even spread to online transportation. With this diversity of public transportation, it should be able to reduce the percentage of traffic jams which is a scourge in several regions in Indonesia. But unfortunately, there are still many people who prefer private modes of transportation. Why did this happen? In this paper, we will discuss what things might make people reluctant to use public transportation modes and prefer private modes of transportation. As well as what factors can improve the quality of public transportation for the comfort and safety of users. In determining the research method, the authors chose to use a descriptive qualitative method with a case study data collection technique. Quoted from several relevant data sources such as journals, books, and websites that discuss the same thing.